Complete Dehydrogenation of N2H4BH3 over Noble‐Metal‐Free Ni0.5Fe0.5–CeOx/MIL‐101 with High Activity and 100% H2 Selectivity. Issue 21 (4th May 2018) - Li, Si‐Jia; Wang, Hong‐Li; Wulan, Ba‐Ri; Zhang, Xin‐bo; Yan, Jun‐Min; Jiang, Qing
Abstract: Efficient and selective dehydrogenation of hydrazine borane (HB), a novel hydrogen storage material with very high hydrogen content (HB, 15.4 wt%), is a key challenge for a fuel‐cell‐based hydrogen economy. However, even using the noble metal catalysts for HB decomposition, the activities are still far from satisfying, to say nothing of non‐noble‐metal‐containing catalysts. In response, as a proof‐of‐concept experiment, herein, noble‐metal‐free NiFe–CeO x nanoparticles are successfully immobilized on an MIL‐101 support without surfactant by a simple liquid impregnation method. Unexpectedly, the resultant Ni0.5 Fe0.5 –CeO x /MIL‐101 catalyst shows good performance, including 100% H2 selectivity, 100% conversion, and record catalytic activity (351.3 h −1 ) for hydrogen generation at mild temperature, which is even better than most of the noble metal heterogeneous catalysts and might be attributed to the good dispersion and uniform particle size of the Ni0.5 Fe0.5 –CeO x nanoparticles due to steric restrictions effect of the MIL‐101 support. Additionally, extending MIL‐101 to some other important kinds of metal–organic framework (MOF) structures, the resultant NiFe–CeO x /MOF catalysts all show good catalytic activity toward HB decomposition, showing the universality of the MOF supported NiFe–CeO x catalysts. Abstract : A noble‐metal‐free Ni0.5 Fe0.5 –CeO x /MIL‐101 catalyst shows supreme catalytic performance for the complete decomposition of a N2 H4 BH3 solution at 343 K. The development of low‐cost and high‐performance catalysts may promote the practical application of N2 H4 BH3 as a promising hydrogen storage material.